Genetics of Early-Onset Alzheimer Dementia. (2003) - Rademakers, Rosa; Cruts, Marc; Van Broeckhoven, Christine
Abstract : Alzheimers dementia (AD) is the most common degenerative disorder of the central nervous system. Although the onset of dementia is above 65 years of age in the majority of the patients (late-onset AD, LOAD), a small subgroup of patients develops AD before 65 years of age (early-onset AD, EOAD). To date 3 genes responsible for EOAD have been identified: the amyloid precursor protein gene (APP), presenilin 1 (PSEN1) and presenilin 2 (PSEN2). PSEN1 is the most frequently mutated EOAD gene with a mutation frequency of 18 to 50% in autosomal dominant EOAD. In addition, the e4 allele of the gene encoding apolipoprotein E (APOE) was identified as a risk factor for both LOAD and EOAD. Many studies reported other susceptibility genes, but the APOE?4 alelle has been the only risk factor that was consistently replicated in all AD populations. Extensive cell biology research in the past ten years led to the hypothesis that the 4 EOAD genes lead to AD through a common biological pathway resulting in abnormal APP processing by subtle different mechanisms. Now, transgenic mice are produced to study the influence of EOAD mutations in vivo, eventually leading to the development of novel therapeutic strategies.